Evaluation of the effect of cryogenic treatment on cutting efficacy of Ni-Ti rotary files - Kamal Amini; Mohammadhossein Fathi; Maryam Zare Jahromi; Amir Mousavi; Azadeh Kamali (Isfahan University of Medical Sciences, 2013)
Introduction: Many efforts have been made to improve Ni-Ti alloy for endodontic use and it has been shown that surface properties and thus cutting efficiency of the rotary files can be improved by processes such as electro-polishing, ion implantation and surface coating. The aim of this study was to evaluate the effect of cryogenic treatment on cutting efficiency of Ni-Ti rotary files.Materials and Methods: In this in vitro study, 60 Ni-Ti rotary instruments (Hero 642, #25, 0.04 taper) were selected and divided into 3 groups of 20. In group I no treatment was used. In group II the instruments were subjected to a deep cryogenic treatment in liquid nitrogen pool (-196°C) for 24 hours and after treatment were immediately tested for cutting efficiency. In group III after cryogenic treatment the temperature of the samples was raised slowly to room temperature for 24 hours. A new piece of test equipment was designed and used. The instruments were attached to the testing machine and rotated in Plexiglas samples for 10 seconds in a working length of 16 mm. The depth of grooves and weight loss of Plexiglas were measured after instrumentation. One-way and two-way ANOVA were used to compare the means of cutting efficacy between the three groups at 95% confidence interval.Results: The instruments which were immediately tested for cutting efficiency had significantly more weight loss and deeper grooves (pweight < 0.001; pgroove = 0.022), indicating better cutting efficiency. However, there was no significant differences between group I and group III in cutting efficacy (p weight = 0.23; p groove = 0.61).Conclusion: The results of this study showed that the surface properties of Ni-Ti alloy could be improved by the cryogenic treatment for a limited period of time after treatment, increasing the cutting efficiency of Ni-Ti rotary instruments. Key words: Plexiglas, Nickel-Titanium alloy, Root canal therapy